2023
DOI: 10.1177/20552076231154380
|View full text |Cite
|
Sign up to set email alerts
|

The positive impact of gamification in imparting nutritional knowledge and combating childhood obesity: A systematic review on the recent solutions

Abstract: Objective This paper reviews the recent gamified interventions that focus on the dietary factor to explore the effectiveness of using gaming elements in combating the prevalence of childhood obesity. Methods Two electronic databases were searched (PubMed and ProQuest); to identify the relevant papers published between 2018 and 2021. The keywords that use to search the entire selected databases were gamification and obesity. There were no restrictions regarding the language. Two independent reviewers screened t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“… 9 11 Previous research on employing gamification elements (GEs) to support healthy eating has shown promising outcomes. 12 16 Notably, GEs like collecting points or completing levels in nonentertainment contexts have proven effective in fostering lasting behavioral changes. 17 , 18 For example, features such as points, levels, and leaderboards make users’ efforts in adopting healthier diets visible, offering supportive feedback and enhancing the overall experience of healthy eating, thus facilitating weight loss.…”
Section: Introductionmentioning
confidence: 99%
“… 9 11 Previous research on employing gamification elements (GEs) to support healthy eating has shown promising outcomes. 12 16 Notably, GEs like collecting points or completing levels in nonentertainment contexts have proven effective in fostering lasting behavioral changes. 17 , 18 For example, features such as points, levels, and leaderboards make users’ efforts in adopting healthier diets visible, offering supportive feedback and enhancing the overall experience of healthy eating, thus facilitating weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the findings from these two systematic reviews [38,39] suggest that no significant differences exist between outcomes derived from apps featuring gamification elements and those lacking them. In the realm of healthy eating, the systematic review conducted by Alghamdi et al [40] highlights that the utilization of gamification elements effectively facilitates imparting nutritional knowledge and combating children obesity. Finally, regarding sleep habits, the utilization of gamification techniques such as goal-based gamification, continuous feedback, and social support has shown promise in positively influencing individuals' sleep patterns, as stated in [41,42].…”
Section: Introductionmentioning
confidence: 99%